Decision-Making of Women Leaders in Government Organizations - Mokat Jetty; Sendouw Recky H. E.; Mantiri Jeane; Rantung Margareth I. R. (SHS Web of Conferences, 2022)
This study aims to determine how the decision-making style of women leaders in government organizations in Manado City. Using a descriptive qualitative approach with the type of case study. Data collection is done through observation, interviews, and documents with triangulation. Data analysis uses an interactive model from Miles and Huberman. The results of the study show that in making decisions, female leaders use normative rules as a reference for action. In general, female leaders, at certain times try to give directions/instructions, involve subordinates, and there a delegation of tasks. Women leaders also have a firm attitude, tend to be strict, very disciplined, and dare to act in very urgent situations to enforce rules for the effectiveness of carrying out their duties. But at a certain time, they can act very meticulously, informatively and communicatively, also responsive and flexible, gentle, friendly, and considerate to subordinates but still authoritative, so that the instinct of a mother radiates in female leaders.